The Effect of Teaching on Entry Behavior of Students in Mathematics - Jude, Iroka; Napoleon, Ishaya Joseph (Darul Yasin Al Sys, 2025)
This study investigates the impact of teaching method on the entry behavior of students in mathematics. The study utilized both quantitative and qualitative data analysis methods with a focus on pre-and post- intervention survey scores. The results indicate that student exposed to interactive and experimental teaching methods showed significant improvements in their attitude motivations, and perceptions towards the subject. The finding suggests that these teaching methods are more effective in influencing entry behavior compared to traditional methods. The study highlights the importance of adopting innovative teaching practices to create a more engaging learning environment and improve, overall learning outcomes. Further research is recommended to explore the long term effect of teaching methods on entry behavior and academic performance in different educational settings.